Pola Komunikasi Mahasiswa Muslim di Kampus Kristen - Dina Fauziyah; Erik Setiawan (UNISBA Press, 2022)
Abstract. Researchers are interested in doing this research because of the phenomenon of Muslim students who decide to study at one of the private universities in the city of Bandung which is affiliated with Christianity. science development. The purposes of this study are 1) To find out the motives of communication by Muslim students of the Faculty of Economics at Maranatha Christian University, 2) To find out the meaning of communication by Muslim students from the Faculty of Economics at Maranatha Christian University. This study uses qualitative research with a phenomenological study approach method that functions to deepen information from individual experiences obtained from the speakers regarding the communication patterns of Muslim students of the Faculty of Economics at Maranatha Christian University. Data collection techniques in this study were in the form of observation, in-depth interviews with 4 informants, and literature study. By using source triangulation collection techniques. The result of this research is that the communication motives of Muslim students of the Faculty of Economics at Maranatha Christian University are divided into 2 (two) types, namely Because of Motive or the